AB0539 Does erythrocyte sedimentation rate reflect disease activity in patients with systemic lupus erythematodes? correlation with acute phase reactants, immunological parameters and proteinuria. (15th June 2017) - Schäfer, VS; Weiß, K; Krause, A; Schmidt, WA
Abstract : Background: Patients with active systemic lupus erythematosus (SLE) are considered to have raised erythrocyte sedimentation rate (ESR) rather than raised C-reactive protein (CRP). Yet published evidence is low for this statement. DsDNA-antibodies, C3 complement, ferritin and proteinuria are also commonly applied to assess SLE. Objectives: Firstly, to assess how ESR correlates with above mentioned laboratory parameters: in general, in the presence of clinical activity and/or infection or in the absence of both. Secondly, to determine if these parameters are associated with disease flare or infections. Methods: A retrospective analysis of patients of a tertiary referral centre with SLE who underwent inpatient treatment between 2006 and 2015. Data on laboratory parameters, infection and disease flare, judged by the treating physician, were extracted. Patients were divided in four SLE groups: flare only (n=147), infection only (n=48), both (n=23), and neither infection nor flare (n=153). ESR was correlated to CRP, ferritin, proteinuria, C3-reduction and raised dsDNA-antibodies for the whole cohort and within each SLE group. Further, the association between all laboratory parameters and a) disease activity with and without infection, b) the presence of infection with and without disease activity, was tested. Results: We identified 203 SLE patients, 26 males, with a total of 371 visits. Mean age was 45.6 years (SD± 16.5 years). Table 1 (top part) shows the correlation coefficients of ESR with the other laboratory parameters. ESR correlated moderately with CRP amongst all groups (r=0.47–0.58); weakly with ferritin in the general and the flare group (r=0.26); and very weakly with C3-reduction and raised dsDNA-antibodies (r<0.2) in each group. Concerning proteinuria, the correlation was weak for all, for flaring and for silent patients (r=0.22 – 0.35), moderate for patients with both infection and activity (r=0.56). There was no correlation in infected patients (r <0.06). Table 1 (bottom part) displays the p-values for the association of parameters with disease activity or infection, respectively. ESR, reduction of C3, proteinuria and raised dsDNA-antibodies were all associated with disease activity in the whole cohort and in the non-infected group; CRP only in non-infected patients. In the infected group, raised dsDNA-antibodies and proteinuria were the only parameters showing significant relation to disease activity. ESR and CRP were significantly associated with infections when looking at all or at inactive patients, but not in active patients. Conclusions: Both, ESR and CRP are elevated in patients with SLE flare and are weakly correlated with other laboratory activity parameters. Thus, while normal CRP argues against infection elevation of ESR and CRP is not sufficient to distinguish between SLE flare and infection. Disclosure of Interest: None declared